2020
DOI: 10.2337/dc19-2227
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21/PDCD4 Proapoptotic Signaling From Circulating CD34+ Cells to Vascular Endothelial Cells: A Potential Contributor to Adverse Cardiovascular Outcomes in Patients With Critical Limb Ischemia

Abstract: In patients with type 2 diabetes (T2D) and critical limb ischemia (CLI), migration of circulating CD34 1 cells predicted cardiovascular mortality at 18 months after revascularization. This study aimed to provide long-term validation and mechanistic understanding of the biomarker. RESEARCH DESIGN AND METHODS The association between CD34 1 cell migration and cardiovascular mortality was reassessed at 6 years after revascularization. In a new series of T2D-CLI and control subjects, immuno-sorted bone marrow CD34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
(55 reference statements)
4
24
0
Order By: Relevance
“…In line with this, recent evidence reports an inhibition of mitophagy (mitochondria-specific autophagy) in PB-MNCs from patients with T2D [ 81 ]. Moreover, tumour suppressor-programmed cell death-4 ( PDCD4 ) overexpression was demonstrated in diabetic PB-MNCs [ 82 •]. These results mirror the recent observation that the inhibition of autophagy associates with an increased expression of PDCD4 in a human cancer cell line [ 83 ].…”
Section: Diabetes-related Limitationssupporting
confidence: 64%
See 4 more Smart Citations
“…In line with this, recent evidence reports an inhibition of mitophagy (mitochondria-specific autophagy) in PB-MNCs from patients with T2D [ 81 ]. Moreover, tumour suppressor-programmed cell death-4 ( PDCD4 ) overexpression was demonstrated in diabetic PB-MNCs [ 82 •]. These results mirror the recent observation that the inhibition of autophagy associates with an increased expression of PDCD4 in a human cancer cell line [ 83 ].…”
Section: Diabetes-related Limitationssupporting
confidence: 64%
“…Several lncRNAs participate in the regulation of stem cell properties including their potential for self-renewal and differentiation, which help in maintenance of normal cell and tissue homeostasis. We have recently reported a T2D-dependent mechanism involving miR-21 downregulation CD34 + MNCs and induction of its inhibitory target PDCD4, a tumor suppressor protein involved in programmed cell death [ 82 •]. We also found that several lncRNAs that act as sponges for miR-21 were overexpressed in CD34 + MNCs and PB of patients with T2D.…”
Section: Diabetes-related Limitationsmentioning
confidence: 79%
See 3 more Smart Citations